Pengaruh Desain Arsitektur terhadap Perilaku dan Proses Pembelajaran di KB & TK Sekolah Alam Quwwatul Ummah Kedungtuban, Blora - Zahira, Aishannada Putri; Utomo, Heru Prasetiyo (Universitas Medan Area, 2025)
Early childhood education provides an important foundation in children's development with fun learning methods and purposeful play. They learn to interact. Talk, and develop motor skills through activities. Sekolah Alam Quwwatul Ummah Kedungtuban located in Blora district offers unique education with a nature-based approach and balanced with religious education for early childhood in the learning process, it is necessary to pay attention to the physical condition of the building behavioral comfort according to the character of the user. Therefore, this research aims to find out how space design, layout, and other architectural elements affect the behavioral comfort of children and their learning process at Sekolah Alam Quwwatul Ummah Kedungtuban. This research uses a qualitative method with data collection through observation and interviews to provide an in-depth understanding of users' perceptions, preferences, and subjective experiences of learning facilities. The results showed that more optimal learning facilities and environments to improve comfort behavior in interacting and children's development while learning is the goal to help children feel comfortable and safe in the environment. For example, easy accessibility, the application of space layout, providing interaction space, and facility design that adjusts the needs of this can affect the psychology of children as a result, children further improve the quality of learning.